HUBUNGAN POLA ASUH ORANG TUA DAN INTERAKSI TEMAN SEBAYA TERHADAP KECANDUAN GAME ONLINE PADA REMAJA - Susilawati, Susilawati; Hendriansyah, Hendriansyah (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2023)
Parenting style and peer interactions influence problems ini adolescent because parents and peer play an important role shaping adolescents attitudes and behavior. Adolescence is a period in which a person's secondary sexual signs have developed and reached sexual maturity. The aim of this research is to determine the relationship between parenting patterns and peer interactions on online game addiction among teenagers in the Sido Mulyo sub-district area, Bengkulu City. This type of research is descriptive correlation with a cross sectional approach. The population in this study were all teenagers who were addicted to playing online games in the Sidomulyo Village area, Bengkulu City. The sampling technique used a total sampling technique of 30 people. The research results showed that the parenting patterns of parents of teenagers who were addicted to online games were democratic with 10 respondents (33.3%), authoritarian with 5 respondents (16.7%) and permissive with 15 respondents (50.0%) and there was a relationship parental care for online game addiction among teenagers in the Sido Mulyo Subdistrict, Bengkulu City with a p value = value 0.028 < α. From the research results, it was found that peer interaction was in the low category of 3 respondents (10.0%), the medium category was 10 respondents (33.3%) and the high category was 17 (56.7%) and there was a relationship between peer interaction and online game addiction in teenagers. in the Sido Mulyo Village Area, Bengkulu City with a p value = value 0.032 < α. It is recommended that Sido Mulyo, Bengkulu, collaborate with the Community Health Center in the area to provide health education to teenagers about online game addiction, so that they can understand the impact of playing online games for too long.